Finger Pulse Profile Investigation Inspired by Ayurveda - Gupta, Spiti (My University, 2012)
Medical science has the primary objective of providing health care to human beings. Various prevailing medical systems have modeled human being in different ways and thus have different approaches to cure the body suffering from any disease. Fortunately all the systems work. Amongst several endeavors made by the researchers worldwide, some point towards rejuvenating the art of diagnosing three basic Ayurvedic human constituents. These are known as doshas namely vata, pitta, kapha. Many Ayurvedic physicians used to diagnose these doshas by feeling the radial artery in the wrist region under the thumb. It is important to document and quantize these Ayurvedic techniques using modern electronic equipment. The fusion would perhaps eternalize this dying art/science of Ayurveda. Using PhotoPlethysmoGraphy (PPG) it is quite possible that specific diagnosis may be reached by studying these finger pulse profiles. In this study the pulse profile of all 10 fingers in 7 healthy subjects were acquired. The pulse profile is recorded by using MP150 data acquisition system by Biopac. For a given subject the auto correlation (correlation of index finger with index finger) was found to be higher than correlation between different fingers (between index finger and middle finger) in most of the cases (67 out of 70). We may safely conclude that the profile of a given subject is unique for the specific finger. This preliminary study opens up a possibility of studying the pulse profile of different fingers in the same person to find the relative features leading to detection of different doshas in a given person. This study was further extended to 6 more subjects and correlation between the corresponding fingers of subject was studied. We came across startling results i:e in all 70 cases without exception the auto correlation for a given finger of subject was always higher than correlation with corresponding finger of any other subject. This study therefore may result in establishing uniqueness of the pulse profile of given subject and it may be used for establishing the three doshas based on ancient ayurvedic science.
ME, EIED
Keywords: Ayurvedic Science; Finger Pulse; PhotoPlethysmoGraphy(PPG); Pulse Profile; Ancient Ayurvedic Science